The Marine Corps War College Strategy Primer Expanded Edition - Marion, Danielle R. (Marine Corps University Press (MCUP), 2022)
The Marine Corps War College Strategy Primer not only provides students an overview of the elements of strategic logic but also introduces a cognitive model for developing and assessing strategy by leveraging innovative design methodologies and other critical and creative thinking approaches. In short, this primer aides in forging strategically minded warfighters who understand how the military instrument fits within a whole-of-government strategy. Only then can MCWAR's historical case studies effectively teach the art and science of the 'strategy bridge,' nesting military options in support of policy ends in shared pursuit of a better peace.